FOCUS OF THE TASK IN ENGLISH TEXTBOOKS OF 2013 CURRICULUM - Irene Monica; Berlin Sibarani (Universitas Negeri Medan, 2022)
The study was aimed to find out and describe focus of the tasks in Englishtextbooks of 2013 curriculum. The researcher used Mileff’s (2009) theory. Thereare three kinds of focus of the tasks, namely skill focus, structure focus andnotional focus. The study used descriptive qualitative design and documentarytechnique to collect the data. The results of the study showed that the researcheronly found one kind of three focus of the tasks, namely skill focus (listening,reading, speaking and writing). In addition, there were four reasons found why thetasks focused on intensive listening, literal reading, responsive and descriptivewriting in the task, namely skill focus (listening, reading, speaking and writing).In addition, there were four reasons found why the tasks focused on intensivelistening, literal reading, responsive speaking and descriptive writing in the tasks.The first reason why the task focused on intensive listening was because to trainstudents’ hearing in getting more understanding of the text. The second reasonwhy the task focused on literal reading was because to make students retell andrecall the information presented in a text. The students acquired the informationdirectly from the text through comprehension question. Third reason why the taskfocused on responsive speaking was because to develop an appropriate shortresponse of students. The last, the reason why the task focused on descriptivewriting was because to help students clarify their understanding of new subjectmatter material.